Nitrogen fertilization in Brachiaria decumbens Stapf grass under degraded soil condition (Research, Society and Development, 2020)
Chemically degraded soils are found all over the world. Fertilization is an essential agronomic technique for recovering fertility and productivity in these areas. In this context, the objective was to recover the productive capacity of a degraded Red Yellow Argisol, grown with Brachiaria decumbens Stapf, in the presence of mineral fertilization with increasing amounts of nitrogen, evaluating the production of plant mass, plant height, tillering and water consumption. The experiment was conducted in a screened shelter and humidity control, according to a completely randomized experimental design. The treatments were organized in a factorial scheme, 6 treatments (without fertilization, 0, 30, 60, 90, 120 of nitrogen; 80 and 50, phosphorus and potassium for all treatments in g vase-1, respectively) corresponding to the amount of fertilizer applied in Kg ha-1, 4 cuts (performed every 30 days, starting 45 days after planting) and 5 repetitions. When fertilizing with 120 Kg ha-1 of nitrogen, it was obtained increase in fresh (655%) and dry (685%) mass when compared to the phytomasses of the treatment without fertilization, there was also an increase in the number of effective tillers and plant height, as the amounts of nitrogen applied increased in the soil. The maximum amount of nitrogen to be applied to the soil, in order to produce phytomass of B. decumbens in the condition of chemical degradation of the soil, obtained in the work was 120 Kg ha-1. In addition, the work allowed us to conclude that fertilization is an inexpensive and very important technique to recover the productive capacity of forage in the micro region of Brejo Paraibano, Northeast Brazil.